Analisis SWOT dalam Identifikasi Mutu Suatu Lembaga Pendidikan - Makmur Syukri; Nur Helmi (Departement of Mathematics Education, 2024)
The world of education in Indonesia, especially at the primary and secondary education levels, is faced with the most important and fundamental educational problem, namely the low quality of education. Various observations and analyzes were carried out, resulting in the conclusion that there are more or less three factors that cause the quality of education in Indonesia to not experience significant improvement, namely: the implementation of education in Indonesia uses an